2009
DOI: 10.1002/ca.20877
|View full text |Cite
|
Sign up to set email alerts
|

Locating the arcuate line of Douglas: Is it of surgical relevance?

Abstract: Ventral hernia formation is a common complication of rectus abdominis musculocutaneous flap harvest. The site and extent of harvest of the flap are known contributing factors. Therefore, an accurate location of the arcuate line of Douglas, which marks the lower extent of the posterior wall of the rectus sheath, may be relevant before harvesting the flap. This study is aimed at determining the position of the arcuate line in relation to anatomical landmarks of the anterior abdominal wall. Arcuate lines were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 2 publications
4
19
0
Order By: Relevance
“…In the remaining 60 patients, a total of 68 TEPP hernioplasties (52 Unilateral and 8 Bilateral) was performed successfully. During the initial telescopic dissection, the posterior rectus canal was always found bounded anteriorly by the variably condensed and thickened posterior epimysium of the rectus abdominis muscle, i.e., the rectusial fascia reported earlier by the author, [19,20] and bounded posteriorly either only by the complete posterior rectus sheath (20% reported in 2010 by Mwachaka et al [21] ; 21% reported in 2017 by Ansari [22,23] ) or by the incomplete posterior rectus sheath (80% reported in 2010 by Mwachaka et al [21] ; 79% reported in 2017 by Ansari [22,23] ) in the upper part above the arcuate line of Douglas and transversalis fascia in the lower part below the arcuate line of Douglas [ Figure 2]. …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In the remaining 60 patients, a total of 68 TEPP hernioplasties (52 Unilateral and 8 Bilateral) was performed successfully. During the initial telescopic dissection, the posterior rectus canal was always found bounded anteriorly by the variably condensed and thickened posterior epimysium of the rectus abdominis muscle, i.e., the rectusial fascia reported earlier by the author, [19,20] and bounded posteriorly either only by the complete posterior rectus sheath (20% reported in 2010 by Mwachaka et al [21] ; 21% reported in 2017 by Ansari [22,23] ) or by the incomplete posterior rectus sheath (80% reported in 2010 by Mwachaka et al [21] ; 79% reported in 2017 by Ansari [22,23] ) in the upper part above the arcuate line of Douglas and transversalis fascia in the lower part below the arcuate line of Douglas [ Figure 2]. …”
Section: Resultsmentioning
confidence: 90%
“…TEPP hernioplasty was carried out consistently by the same 3-midline port technique [ Figure 1] as reported earlier by the author. [15][16][17][18][19][20][21][22] Dissection in the posterior rectus canal was performed unhurriedly with gentle controlled to-and-fro movements of the 0º 10-mm telescopic. Further dissection in the pelvis and inguinal region was carried out by blunt/sharp instrument dissection under low settings of electrocautery.…”
Section: Section: Surgerymentioning
confidence: 99%
“…[7][8][9][10][11] In contrast to the general belief, anatomy of the groin is reported to be complex, especially in presence of anatomic variations reported by several investigators that received little/no attention of anatomists and practicing surgeons alike. 8,10,[12][13][14][15] In 2001, Robert Bendavid declared that 'Nothing goes as far forward preventing complications as the surgeon's awareness and fear of them'. 16 Recently the author has reported an exhaustive laparoscopic study on the anatomic variations in the posterior rectus sheath (PRS) observed during the TEPP hernioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may not be an optimal criterion for stoma siting as was also evident from a high incidence the unsatisfactory siting of the stoma in 36-55% of patients in different categories of Al-Momani's series [5]. This may be a reflection of two factors, viz., firstly, the arcuate line position is reported to be highly variable [10-12, 17,18,21,22, 42-46], being significantly higher in the overweight/obese individuals [12,17,43,47]; secondly, the level of the anterior interspinous line may also vary depending upon the body habitus and gender of the individual. Present study is limited by absence of female patients.…”
Section: Discussionmentioning
confidence: 99%